Strategic Planning Behaviors and Their Effects on Public Construction Management Performance - Do, Van Thuan; Nguyen, Luong Hai; Nguyen, Phuong Anh; Tran, Tuan Phong (International Journal of Sustainable Construction Engineering and Technology, 2025)
Effective planning behaviors are critical to the success of public construction investment, particularly within institutional environments marked by regulatory complexity and fiscal constraints, yet prior research has largely overlooked the specific functional behaviors involved in planning processes for public sector infrastructure development. This study conceptualizes planning behaviors as a multidimensional construct and empirically examines their impact on management performance, identifying eight behavioral dimensions—ranging from guideline dissemination to capital allocation and project selection—through a survey of 136 experienced public sector professionals analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Capital Allocation Planning (PL5) and Project Selection (PL6) significantly and positively influence management performance, while Capacity of Investment Balance (PL7) has a significant but negative effect; other behaviors, such as Planning Guidelines (PL1), Plan Consistency (PL4), and Execution Descriptions (PL8), lack direct effects but play crucial mediating roles through PL5 and PL6. These results highlight the differentiated impact of planning actions, emphasizing the need for a multi-level behavioral framework to enhance planning effectiveness, improve managerial practices, reform policies, and advance theoretical understanding of infrastructure governance in public investment.